Application of quaternary ammonium salt polymer in thermoelectric material
By using quaternary ammonium polymer as dispersant, the problem of poor dispersion of carbon nanotubes in thermoelectric materials is solved, and the stable dispersion of carbon nanotubes and the film preparation with high thermoelectric properties is achieved.
Patent Information
- Application Number
- CN202311133171.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
Carbon nanotubes are difficult to disperse uniformly in organic solvents or water, and their strong aggregation ability leads to the dispersion not being maintained for a long time, limiting their application in thermoelectric materials.
Quaternary ammonium salt polymer is used as a dispersant, and by adjusting the ratio of dispersant to carbon nanotubes, a stable dispersion liquid is formed with the carbon nanotubes by regulating the ratio of dispersant to carbon nanotubes, thereby improving the dispersion and thermoelectric properties of carbon nanotubes.
The dispersion and thermoelectric properties of carbon nanotubes were significantly improved, and carbon nanotube films with high thermoelectric properties were prepared, enriching the types of carbon nanotube cationic dispersants.
Smart Images

Figure CN119552285A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to application of a quaternary ammonium salt polymer in a thermoelectric material, and in particular to a thermoelectric material prepared by effectively dispersing carbon nanotubes through a novel quaternary ammonium salt polymer, so that the thermoelectric material has significantly improved thermoelectric performance. Background Art
[0002] Energy shortage and environmental pollution are major issues related to the sustainable development of human society and have attracted great attention from the world. The energy that humans mainly rely on, such as traditional fossil resources such as oil, coal and natural gas, is extremely precious and non-renewable. In industrial production and daily life, there is a widespread and serious phenomenon of "heat energy is inevitably generated but discarded" (such as industrial waste heat, automobile exhaust heat, etc.); in addition, most of the geothermal energy and human body heat are also wasted in vain. Research and development of clean energy has become a key area of global scientific research. Thermoelectric materials are an environmentally friendly functional material that uses the movement of solid internal carriers to achieve direct conversion between thermal energy and electrical energy. When used, no transmission parts are required. It has the advantages of small size, light weight, no noise, no pollution, long life, and easy control, and has attracted much attention. It can not only be used for heat recovery power generation and refrigeration, but also for health monitoring sensors that use body temperature.
[0003] In recent years, with the rapid development of thermoelectric materials, carbon nanotubes (CNTs) have become a research hotspot in the field of thermoelectric materials due to their excellent charge transport capacity, large specific surface area, flexibility, light weight, excellent mechanical strength and other characteristics. However, due to the strong agglomeration nature of carbon nanotubes, it is difficult to disperse them evenly in organic solvents or water. Moreover, even if a good dispersion is formed with the assistance of a dispersant, its dispersibility cannot be maintained for a long time due to its strong aggregation ability. It can be seen that the dispersibility problem of carbon nanotubes has seriously restricted its application, and the development of new and efficient dispersants has vital scientific significance and practical value.
[0004] At present, the dispersants used to disperse carbon nanotubes are mainly polymeric and small molecule types. There have been many reports on the research of common small molecule dispersants such as sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (MSBS), dodecyltrimethylammonium bromide (DTAB), hexadecyltrimethylammonium bromide (CTAB) and other ionic dispersants. However, the materials of small molecule carbon nanotube dispersants are mostly anionic surfactants, and the types of cationic surfactants are rare, with only a few and applicable solvents basically limited to water. In addition, the most widely used polymer dispersant is anionic poly (sodium styrene sulfonate) (PSSNa). Although this dispersant can disperse and stabilize carbon nanotubes in water or alcohol by forming π-π interactions with the carbon nanotube wall, it will significantly reduce the Seebeck coefficient of carbon nanotubes. In addition, since its cation is an inorganic metal ion, its solubility in other organic solvents is greatly reduced, thereby limiting its application scenarios. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A quaternary ammonium salt polymer is used in a thermoelectric material. The structural formula of the quaternary ammonium salt polymer is shown in Formula I:
[0007]
[0008] In formula I, R is selected from hydrogen atom, C 1-20 Alkyl, C 3-20 Cycloalkyl, 3-20 membered heterocyclic group, C 6-20 Aryl or 5-20 membered heteroaryl; said C 6-10 Aryl or 5-20 membered heteroaryl is optionally substituted with C 1-20 Alkyl, C 3-20 Cycloalkyl substitution;
[0009] When R is not H, m is the number of substituents R, selected from an integer of 1-5;
[0010] n is selected from 1-100, for example, 10, 50, or 100.
[0011] Exemplarily, the structural formula of the quaternary ammonium salt polymer is shown in Formula I-1:
[0012]
[0013] In formula I, n is selected from 1-100, for example, 10, 40, 50, or 100.
[0014] According to an embodiment of the present invention, the quaternary ammonium salt polymer is a white solid.
[0015] The present invention also provides a thermoelectric material, which comprises a dispersant and a carbon material, wherein the dispersant comprises the quaternary ammonium salt polymer.
[0016] According to an embodiment of the present invention, the carbon material is selected from carbon nanotubes. Preferably, the carbon nanotubes are selected from single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0017] According to an embodiment of the present invention, the mass ratio of the dispersant to the carbon material is (1-10):1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.
[0018] According to an embodiment of the present invention, the thermoelectric material may be a thin film.
[0019] The present invention also provides a method for preparing the above thermoelectric material, which specifically comprises the following steps:
[0020] (1) adding the dispersant to an organic solvent and stirring uniformly to obtain a dispersant solution;
[0021] (2) adding the carbon material to the dispersant solution obtained in step (1) to obtain a suspension;
[0022] (3) The suspension obtained in step (2) is subjected to a desolventizing treatment to obtain a thermoelectric material.
[0023] According to an embodiment of the present invention, in step (1), the amount of the organic solvent used is not specifically limited, as long as it can completely dissolve the dispersant.
[0024] Illustratively, the usage ratio of the dispersant and the organic solvent is (1-50) mg:(1-40) mL, for example, 5 mg:30 mL, 25 mg:30 mL.
[0025] According to an embodiment of the present invention, in step (1), the organic solvent is selected from N,N-dimethylformamide (DMF) and acetonitrile, preferably acetonitrile.
[0026] According to an embodiment of the present invention, in step (2), the carbon material has the meaning as described above, preferably carbon nanotubes (such as single-walled carbon nanotubes and / or multi-walled carbon nanotubes), and more preferably single-walled carbon nanotubes.
[0027] According to an embodiment of the present invention, in step (2), the mass ratio of the dispersant to the carbon material is 10:1 to 1:1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.
[0028] According to an embodiment of the present invention, in step (2), the suspension may be further subjected to ultrasonic dispersion, for example, ultrasonic dispersion for 0.5 to 2 h, and for example, for 0.5 to 1 h.
[0029] According to an embodiment of the present invention, in step (2), the solid content of the suspension is not specifically limited, as long as a uniform and stable suspension can be obtained, for example, the solid content is 30% to 40%.
[0030] According to an embodiment of the present invention, in step (3), the desolventizing treatment can be performed by methods known in the art.
[0031] Exemplarily, when the thermoelectric material is a thin film, the desolventizing treatment includes: filtering the suspension under reduced pressure to obtain a black solid filter membrane; washing the black solid filter membrane and drying it. Further, the washing is performed with the same organic solvent as used in step (1), for example, washing three times. Further, the drying conditions include vacuum drying at 40 to 100°C, for example, drying at 50°C for 24 hours.
[0032] The present invention also provides applications of the quaternary ammonium salt polymer and / or thermoelectric thin film material, for example, in the field of thermoelectricity.
[0033] Beneficial Effects
[0034] The invention provides a novel quaternary ammonium salt polymer dispersant, which has the advantages of convenient synthesis, low cost and good solubility in organic solvents. The invention cleverly utilizes the homopolymerization reaction of cationic compounds to prepare a quaternary ammonium salt polymer with novel structure and simple synthesis. The invention utilizes the quaternary ammonium salt cationic polymer as a dispersant for the dispersion of carbon nanotubes. By adjusting the ratio of the dispersant to the carbon nanotubes, a carbon nanotube dispersion with good stability can be obtained, which greatly improves the problem of easy agglomeration in the dispersion process of the carbon nanotubes, thereby preparing a carbon nanotube film with higher thermoelectric performance, and effectively improving the thermoelectric performance of the carbon nanotubes. The quaternary ammonium salt cationic polymer of the invention enriches the types of carbon nanotube cationic dispersants.
[0035] The quaternary ammonium salt polymer provided by the invention is a non-metallic ion type cationic polymer dispersant, which has good solubility in an organic solvent and can be used to prepare a carbon nanotube dispersion liquid with good dispersibility. The synthesis method of the quaternary ammonium salt polymer provided by the invention is simple to operate, low in cost, high in efficiency and environmentally friendly, and is convenient for large-scale preparation.
[0036] The present invention also provides a method for preparing a thermoelectric thin film material which is easy to operate and environmentally friendly, and effectively improves the thermoelectric performance of the carbon nanotube film. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the synthesis route of the vinylbenzylpyridinium salt polymer of Example A. DETAILED DESCRIPTION
[0038] [Preparation method of quaternary ammonium salt polymer]
[0039] The present invention also provides a method for preparing the quaternary ammonium salt polymer, which specifically comprises:
[0040] (1) adding a first reactant and a second reactant into a first solvent to carry out a first reaction to obtain a first product;
[0041] (2) adding the first product obtained in step (1) to a second solvent, adding a third reactant under stirring, and performing a second reaction to obtain a second product;
[0042] (3) dissolving the second product obtained in step (2) in a solvent, adding an initiator, causing a polymerization reaction, and obtaining the quaternary ammonium salt polymer.
[0043] According to an embodiment of the present invention, the first reactant is selected from 4-vinylbenzyl chloride.
[0044] According to an embodiment of the present invention, the second reactant is selected from pyridine.
[0045] According to an embodiment of the present invention, in step (1), the conditions of the first reaction include: reaction at 40-60°C for 1-20h, for example, reaction at 50°C for 10-15h.
[0046] According to an embodiment of the present invention, in step (1), the reaction is carried out under stirring conditions.
[0047] According to an embodiment of the present invention, in step (1), after the first reaction, a precipitation solvent is added to precipitate the first product, and the first product solid is obtained after separation. Preferably, the separation can be carried out by a method known in the art, such as vacuum filtration. Preferably, after separation, the first product solid can also be washed and / or dried.
[0048] According to an embodiment of the present invention, the precipitation solvent is selected from diethyl ether.
[0049] According to an embodiment of the present invention, in step (1), the first product has a structure as shown in formula A, which is a light yellow solid.
[0050]
[0051] According to an embodiment of the present invention, in step (2), the third reactant is selected from NaBF4.
[0052] According to an embodiment of the present invention, in step (2), the conditions of the second reaction include: reacting at 10-30° C. for 10-50 h, such as stirring at room temperature for 48 h.
[0053] According to an embodiment of the present invention, in step (2), after the second reaction, the filtrate is filtered to obtain a filtrate, and then a precipitation solvent is added to the filtrate to precipitate the second product, and the second product solid is obtained after separation. Preferably, the separation can be carried out by a method known in the art, such as vacuum filtration. Preferably, after separation, the second product solid can also be washed and / or dried.
[0054] According to an embodiment of the present invention, in step (1) or step (2), washing can be performed using a precipitation solvent.
[0055] According to an embodiment of the present invention, in step (2), the second product has a structure as shown in formula B, which is a white solid.
[0056]
[0057] According to an embodiment of the present invention, in step (3), the polymerization reaction is carried out under the protection of an inert gas, and the inert gas can be selected from those known in the art, such as Ar.
[0058] According to an embodiment of the present invention, in step (3), the conditions of the polymerization reaction include: a reaction temperature of 50-90° C. (for example, 60° C.); and a reaction time of 10-24 h.
[0059] According to an embodiment of the present invention, in step (3), after the polymerization reaction, the reaction solution is dropped into an alcohol solvent to precipitate a solid substance, which is the quaternary ammonium salt polymer.
[0060] According to an embodiment of the present invention, in step (3), after the solid matter is precipitated, the solid is collected, and optionally washed and / or dried. Preferably, the collection can be carried out by a method known in the art, such as vacuum filtration. Preferably, in step (3), washing can be carried out using an alcohol solvent.
[0061] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0062] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0063] Embodiment A:
[0064] In this example, P3-CCR-H is prepared by referring to Example 1 in patent document CN116414012A, i.e., p-vinylbenzylpyridinium salt polymer. The synthetic route is as follows: Figure 1 As shown: 4-vinylbenzyl chloride is used as a starting material, and an intermediate compound a is obtained by reacting with pyridine; an intermediate compound b is obtained by an ion exchange reaction between NaBF4 and the intermediate compound a; and a target product c, p-vinylbenzylpyridinium salt polymer, is obtained by homopolymerizing the compound b in a DMF solvent under the initiation of AIBN, which specifically includes:
[0065] (1) Synthesis of intermediate compound a: 4-vinylbenzyl chloride (5.64 ml, 40 mmol) and pyridine (3.2 ml, 40 mmol) were added to 40 ml of acetonitrile solvent, stirred at 50°C and reacted overnight. The reaction mixture was slowly poured into ether, filtered, and the solid was washed three times with deethyl ether. The collected solid was vacuum dried at 60°C for 12 h to obtain 8.7 g of light yellow crystalline powder compound a, with a yield of 87%. 1H NMR(400MHz,Deuterium Oxide)δ8.83(d,J=5.5Hz,2H),8.48(t,J=7.8Hz,1H),7.99(t,J=7.1Hz,2H),7.50(d,J=8.3Hz,2H),7.37(d ,J=8.2Hz,2H),6.72(dd,J=17.7,11.0Hz,1H),5.82(d,J=17.7Hz,1H),5.72(s,2H),5.30(d,J=11.6Hz,1H).
[0066] (2) Synthesis of intermediate compound b: The intermediate product a (5.13 g, 24 mmol) and sodium tetrafluoroborate (2.82 g, 26 mmol) were added to 20 ml of acetone solvent respectively and stirred at room temperature for 2 days. The reaction mixture was filtered under reduced pressure to obtain a light yellow filtrate, which was precipitated with ether, filtered, and the solid was washed three times with ether. The collected solid was vacuum dried at room temperature for 12 h to obtain 6.2 g of milky white solid b, with a yield of 97.8%.
[0067] (3) Synthesis of target product c: Add intermediate compound b (4.50 g, 18.91 mmol) and AIBN (45 mg, 0.27 mmol) to a reaction tube, inject 8 ml of ultra-dry DMF into the reaction tube, replace with Ar gas three times, react at 60°C for 10 h, and then pour the reaction solution into ether for precipitation to obtain a viscous solid. After filtering, add the solid to ethanol solvent and stir well to obtain a white solid. Filter and vacuum dry the collected solid at 50°C for 24 h to obtain 4.26 g of white solid, which is the target product, p-vinylbenzylpyridinium salt polymer, with a yield of 94.67%. Its structure is shown in Formula I.1 H NMR (400MHz, DMSO-d6) δ9.00(s,2H),8.58(d,J=35.0Hz,1H),8.10(s,2H),7.16(s,2H),6.44(d,J=45.8Hz,2H),5.67(s,2H),1.98–0.68(m,3H).
[0068] Embodiment 1:
[0069] The preparation method of the composite carbon nanotube film is as follows:
[0070] (1) Add 25 mg of p-vinylbenzylpyridinium salt polymer dispersant to 35 mL of acetonitrile and stir at room temperature until the solid is dissolved;
[0071] (2) 5 mg of carbon nanotubes (NTP8012, purchased from Shenzhen Nanotube Co., Ltd., the same below)
[0072] Add to the solution obtained in step (1);
[0073] (3) ultrasonically dispersing the suspension obtained in step (2) for 1 h;
[0074] (4) The suspension obtained in step (3) was filtered under reduced pressure to obtain a black solid filter membrane. The black solid filter membrane was washed and vacuum dried at 50° C. for 24 h to obtain a uniform composite carbon nanotube film.
[0075] Embodiment 2:
[0076] This embodiment prepares a composite carbon nanotube film by referring to the method of embodiment 1, except that the steps
[0077] (1), 5 mg of p-vinylbenzylpyridinium salt polymer dispersant was added to 35 mL of acetonitrile; the remaining steps were the same as those in Example 1 to prepare a uniform composite carbon nanotube film.
[0078] Comparative Example 1:
[0079] The preparation method of the carbon nanotube film of this comparative example is as follows: (1) 5 mg of carbon nanotubes are added to 35 mL of acetonitrile;
[0080] (2) ultrasonically dispersing the suspension obtained in step (1) for 1 h;
[0081] (3) The suspension obtained in step (2) is filtered under reduced pressure to obtain a black solid filter membrane. The black solid filter membrane is washed and vacuum dried at 50° C. for 24 h to obtain a uniform carbon nanotube film.
[0082] Test Example 1
[0083] The films prepared in the above embodiments and comparative examples were taken and their thermoelectric performance parameters were tested using an MRS-3RT thermoelectric performance tester (Wuhan Jiayitong Technology Co., Ltd.), including conductivity, Seebeck coefficient, power factor (the power factor is not directly tested by the instrument, but is calculated based on conductivity and Seebeck coefficient, and there is a calculation formula), etc. The test results are recorded in Table 1.
[0084] Test Example 2
[0085] The suspensions after ultrasonic dispersion in the above examples and comparative examples were observed for sedimentation after 30 days of placement, and the test results were recorded in Table 1, where: √ represents very good; △ represents acceptable; and × represents the worst.
[0086] Table 1. Test results
[0087]
[0088] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of a quaternary ammonium salt polymer in a thermoelectric material, characterized in that: The structural formula of the quaternary ammonium salt polymer is shown in Formula I: In formula I, R is selected from hydrogen atom, C 1-20 Alkyl, C 3-20 Cycloalkyl, 3-20 membered heterocyclic group, C 6-20 Aryl or 5-20 membered heteroaryl; said C 6-10 Aryl or 5-20 membered heteroaryl is optionally substituted with C 1-20 Alkyl, C 3-20 Cycloalkyl substitution; When R is not H, m is the number of substituents R, selected from an integer of 1-5; n is selected from 1-100.
2. The use according to claim 1, characterized in that: The structural formula of the quaternary ammonium salt polymer is shown in Formula I-1: In formula I, n is selected from 1-100.
3. The use according to claim 1 or 2, characterized in that: The quaternary ammonium salt polymer is a white solid.
4. A thermoelectric material, characterized in that: The thermoelectric material comprises a dispersant and a carbon material, wherein the dispersant comprises the quaternary ammonium salt polymer described in any one of claims 1 to 3.
5. The thermoelectric material according to claim 4, characterized in that The carbon material is selected from carbon nanotubes. Preferably, the carbon nanotubes are selected from single-walled carbon nanotubes or multi-walled carbon nanotubes.
6. The thermoelectric material according to claim 4 or 5, characterized in that: The mass ratio of the dispersant to the carbon material is (1-10):
1. Preferably, the thermoelectric material is a thin film.
7. The method for preparing a thermoelectric material according to any one of claims 4 to 6, characterized in that: The specific steps include: (1) adding the dispersant to an organic solvent and stirring uniformly to obtain a dispersant solution; (2) adding the carbon material to the dispersant solution obtained in step (1) to obtain a suspension; (3) The suspension obtained in step (2) is subjected to a desolventizing treatment to obtain a thermoelectric material.
8. The preparation method according to claim 7, characterized in that: In step (1), the usage ratio of the dispersant to the organic solvent is (1-50) mg:(1-40) mL. Preferably, in step (1), the organic solvent is selected from N,N-dimethylformamide and acetonitrile.
9. The preparation method according to claim 7 or 8, characterized in that: In step (2), the mass ratio of the dispersant to the carbon material is 10:1 to 1:
1. Preferably, in step (2), the suspension is further subjected to ultrasonic dispersion. Preferably, in step (2), the solid content of the suspension is 30% to 40%.
10. Use of the thermoelectric thin film material according to any one of claims 4 to 6 in the thermoelectric field.
Citation Information
Patent Citations
Electropositive polymer charge control agent as well as preparation method and application thereof
CN116414012A
Cited By
Electropositive polymer charge control agent as well as preparation method and application thereof
CN116414012A
A positive polymer charge control agent, its preparation method and use
CN116414012B